(untitled) (Journal of Forensic Medicine & Toxicology, 2012)
Exhumation is a lawful disinterment or digging out of an already buried body from the grave. It is usually done for the purpose of identification or to determine the cause of death when foul play is suspected. In India it is quite rare as the Hindus who form a majority of population cremate their dead with in a few hours of death. In this paper a case is presented where a married lady along with her paramour killed her husband. The body of husband was buried in the ground, near the village pound outside her resident. The matter remained silent for few months but latter on the police got the secret information from a villager and acted swiftly. The order for exhumation was procured by the police from magistrate. On disinterment the body was recovered from the burial site, it was identified and later on it was shifted to the Deptt. Of Forensic Medicine, Govt. Medical College, Amritsar for complete medico-legal Autopsy. After performing autopsy, the cause of death was established. In this paper main focus will be on the Method of exhumation along with its photographic presentation.